Efficacy of Employment of Isotonic Sterofundin after Experimental Hemorrhagic Shock - A. Yu Yakovlev; V. V. Kichin; V. O Nikolsky; G. V. Kalentyev; D. V., Ryabikov; M. A. Ryabikova; D. M Protasov; T. A. Galanina; A. Yu. Smerkalov; O. S. Evdokimova (Общая реаниматология, 2013)
Objective: to perform an experimental study of the effect of isotonic sterofundin on the morphology of the myocardium, kidney, lung, pancreas, liver, and brain in the late period after hemorrhagic shock. Material and methods. Hemorrhagic shock was induced in 36 male Wistar rats weighing 230—250 g by acute massive blood loss (AMBL) of 2.5 ml/100 g at a rate of 2 ml/min. An hour after AMBL, hypovolemia was replenished to 200% volume for 60 min with Ringer solution and isotonic sterofundin in control and experimental groups, respectively. Then the blood was reinfused at 70% volume of its loss. The magnitude of morphological changes was estimated 3 days following AMBL. Specimens harvested from organs of euthanized animals were examined histologically and images were recorded using a ^Vizo-103 microvisor. Results. The experimental studies demonstrate significant structural damage of tissues within target organs following traditional infusion therapy with polyionic crystalloid solutions that may cause development of multiple organ dysfunction. Malate-containing solution of sterofundin reduces the degree of organ structural damages that may prevent multiple organ dysfunction in the posthemorrhagic period. Key words: acute massive blood loss, hemorrhagic shock, malate, sterofundin isotonic, multiple organ dysfunction.